Estimation of vestibular depth: An observational cross-sectional study - Tanya Nandkeoliar; Ashish Kumar; Sachidananda Chungkham; Sinam Subhaschandra Singh (Wolters Kluwer Medknow Publications, 2023)
Background: The vestibular depth (VD) varies to a great extent among individuals and at different points of reference. The normal range of depth of the vestibule at different areas in the mouth remains to be established. Aim: The primary objective of this study is to assess the average VD around different teeth in the maxilla and the mandible. Furthermore, an attempt has been made to identify the various ranges of VD and understand what could be suggestive of a normal VD. Materials and Methods: The participants included were divided into four age groups, i.e., 6-14 years (Group 1), 15-30 years (Group 2), 31-50 years (Group 3), and >50 years (Group 4). Further, the subjects were grouped into subgroup A, periodontally healthy and subgroup B, gingival recession (GR). Group 1, 2, and 3 included 30 subjects each in subgroup A, while Group 4 subgroup B had 18 subjects. In case of subgroup B, Group 2 included 9 subjects, Group 3-31 subjects, and Group 4-30 subjects. Measurements included the depth of vestibule from 2 reference point, i.e., gingival margin (GM) and incisal edge (IE). Results: In subgroup A, the average VD from GM was found to be the least in the Group 1 i.e., 6-14 years (9.2 mm ± 4.26 in maxilla and 7.01 mm ± 3.14 in the mandible) and the highest in the Group 4 i.e., >50 years (12.06 mm ± 2.73 in maxilla and 10.08 mm ± 2.58 in the mandible). In the case of subgroup B, the least depth from GM was found in the Group 3 i.e., >30-50 years (9.44 mm ± 2.73 in the maxilla and 8.32 mm ± 1.7 in the mandible) and the maximum depth in the Group 4 (>50 years) (11.28 ± 2.31 in maxilla and 9.42 ± 2.87 in the mandible). Conclusion: The study provides a range of VD s in different areas of the mouth in periodontally healthy and individuals with GR, which will contribute to constitute a normal range of VD.